2020
DOI: 10.1080/19320248.2020.1830221
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Food Insecurity among US Adults during the COVID-19 Pandemic

Abstract: This research examines the intersection of social vulnerability, risk, and their impact on individual food insecurity odds during the COVID-19 pandemic. Data come from a national, poststratification weighted sample of U.S. adults (n = 10,368). Logistic regression analysis confirms what we hypothesizedsocially vulnerable, fearful, persons in poorer health, and those with higher levels of depressive and anxiety symptoms have higher food insecurity odds. Findings underscore the importance of redesigning food syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
122
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 44 publications
13
122
2
1
Order By: Relevance
“…In 2019, the national prevalence of household food insecurity in the United States—defined as not having access by all people at all times to enough food for an active, healthy life—was 10.5% [ 6 ]. However, the COVID-19 pandemic dramatically reversed previous declines in food insecurity, and the prevalence of household food insecurity rose dramatically in the Spring of 2020, with reports as high as 38% in late March [ 7 , 8 , 9 ]. Given this increase, it is critical that parent feeding practices be examined under the context of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the national prevalence of household food insecurity in the United States—defined as not having access by all people at all times to enough food for an active, healthy life—was 10.5% [ 6 ]. However, the COVID-19 pandemic dramatically reversed previous declines in food insecurity, and the prevalence of household food insecurity rose dramatically in the Spring of 2020, with reports as high as 38% in late March [ 7 , 8 , 9 ]. Given this increase, it is critical that parent feeding practices be examined under the context of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Across the country, almost 14% of adults reported not having enough to eat in the last seven days in early December 2020 compared to the pre-pandemic rate of 3.7% for the previous year (2019) [ 3 ]. Other studies have reported increases in food insecurity rates in various parts of the country during the pandemic [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity is growing due to the economic crisis caused by the COVID-19 pandemic, and the number of people facing food insecurity worldwide could double by the end of 2020 ( World Food Program, 2020 ). Both developing and developed countries are facing the same situation due to increased food insecurity during the COVID-19 pandemic, while vulnerable and low-income population groups are more severely affected ( Fitzpatrick, Harris, & Drawve, 2020 ). Government authorities must play a vital role in supporting access to healthy food ( FAO, 2020c ).…”
Section: Impact Of the Covid-19 Pandemic Crisis On The Food Supply Symentioning
confidence: 99%